Review (Res Medica, 2014)
It was with mixed feelings that we came to the first part of our sale at Sotheby’s. We could not be but pleased that four years of careful thought and debate, then of negotiation, had come to an end; but the pleasure was mixed with sadness that the library was being split up irrevocably under the auctioneer’s hammer. Economic logic was not enough to fully cover the feeling that had bound the books to the Society’s history.The sale began at 11am precisely, on Monday, 10th February. By 1.30pm the same day the books had realised £21,000; and on the following day a further £18,000 had accrued in less than two hours. The total sum from the first sale therefore does much to justify the decision to sell by auction, and justifies completely our hopes that the total sale should reach something more than £100,000, if not equalling the £ 120,000 that was turned down early last year when an American institution had offered to buy the whole collection.The principle that the books should be available to all, and particularly British collectors has been justified too. Although the biggest buyers were naturally the dealers Dawson and Rota, a number of the more important works were in fact acquired by private collectors.  Most notable was the successful bidding by a London professor of Chemistry for nearly all our collection of the works of Boyle as well as for other works on chemistry such as Davy’s “Researches Chemical and Philosophical” and Clarke’s “The Gas Blowpipe or Art of Fusion”.